Penentuan Biaya Optimum pada Permasalahan Transportasi Seimbang dengan VAM dan MODI - Hendy Tannady (Universitas Bunda Mulia, 2017)
Transportation is fundamentally in our life, not only to distributes of goods and commodities but also to distributes humans. Transportation problem is the problem that we often encounter. This study is further research from previous research conducted by Onianwa and Sadiq from Ambrose Alli University, Nigeria. This study tried to manipulate the inter-facility transport from the discussion of the previous research with Vogel Approximation Method (VAM) and Modified Distribution (MODI). The results show that VAM provides transportation cost for 11.050 ( 500 lower than NWCR) and equal to the output of the AAU software that used previously.Keywords: Transportation, Vogel Approximation, Modified Distribution.